Comparison of methodological data measurement limits in CD4+ T lymphocyte flow cytometric enumeration and their clinical impact on HIV management. Issue 4 (23rd April 2013) - Whitby, Liam; Whitby, Alison; Fletcher, Matthew; Helbert, Matthew; Reilly, John T.; Barnett, David
Abstract : UK NEQAS for Leucocyte Immunophenotyping, an ILAC G13:2000 accredited External Quality Assessment (EQA) organization, with over 3000 international laboratories participating in 14 programmes, issues 2 proficiency testing samples of stabilized whole blood to 824 participants in the Immune Monitoring (lymphocyte subset) programme every two months. We have undertaken a study of 58, 626 flow cytometric absolute CD4 + T lymphocyte count data sets from these laboratories over a 12‐year‐period (2001–2012) to determine counting method variation in data measurement limits and how this could influence the clinical management of HIV patients. Comparison of relative error and 99.9% confidence limits for absolute CD4 + T lymphocyte values was undertaken using dual platform (DP) and single platform (SP) data and showed that the SP consistently outperformed DP, giving lower relative errors and confidence limits at clinically significant absolute CD4 + T lymphocyte counts. Our data shows that absolute CD4 + T lymphocyte counts should be obtained using single platform technology to reduce the variability at clinically relevant levels. On data where results (irrespective of platform) were below the international treatment threshold of 350 cells/μl, there was no significant misclassification between either SP or DP techniques meaning most patients would receive the correct treatment at the correct time. However, results that were above the treatment level of 350 cells/μl had a significant difference ( P = 0.04) between DP and SP platforms, suggesting patients monitored using DP technology were 20% more likely to start therapy prematurely than those monitored with SP technology. © 2013 International Clinical Cytometry Society